CONDITION OF BLOOD SYSTEM IN CHILDREN WHO RESIDE IN THE DISTRICT OF ASTRAKHAN GAS COMPLEX - I.A. Aksenov; A.A. Dzhumagaziev (Вопросы современной педиатрии, 2008)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2008; 7(2):144-145)